Effect of silane functionalization on mechanical properties of carbon fiber reinforced composites - Brar, Ramneet Singh (My University, 2016)
In this work, unidirectional carbon fibers are treated with silane coupling agents and the effect of surface treatment on mechanical properties of fiber reinforced epoxy composites was studied. The fiber surface modification was carried out using wet method. The silane functional groups and concentration of the silane influence the grafting of silane as confirmed by FTIR studies. The effect of reaction time and change in silane concentration influenced the mechanical properties of the composites. The composite containing the carbon fiber treated with 3-Amino propyl triethoxy silane at 1.5% concentration (v/v) with treatment time 30 minutes possess the best mechanical properties with an increase of 33.6%, 32.38%, 33.72% in flexural modulus, tensile modulus and inter laminar shear strength respectively from the neat CFRC. The flexural and ILSS properties with treatment time 30 minutes increase in following order: Neat CFRC< GPS(1.5)< GPS(2.5)< APS(2.5)< APS(1)< GPS(1)< APS(1.5). The tensile properties with treatment time 30 minutes increase in the following order: Neat CFRC< GPS(1.5)< APS(2.5)< APS(1)< GPS(2.5)< GPS(1)< APS(1.5). Finite element analysis is done using ANSYS 15.0 software comparing the experimental deformation of the tensile tested samples and the simulated deformation. Results indicated that the experimental values match reasonably validating the experimental results.
Keywords: Carbon fiber reinforced composite; Silanes; Mechanical properties; Finite element analysis